Future accelerator projects: new physics at the energy frontier - Canepa, Anadi; D’Onofrio, Monica (Frontiers in Physics, 2023)
High energy colliders provide direct access to the energy frontier, allowing to search for new physics at scales as high as the machine’s center-of-mass energy, perform precision measurements of the SM parameters including those related to the flavor sector, and determine the Higgs boson properties and their connection to electroweak symmetry breaking. Each proposed future collider option has its own specific science goals and capabilities, depending on the designed running energy(ies) amongst other parameters. In this paper, an overview of the discovery potential of future circular and linear colliders is presented. Results from searches for beyond the Standard Model phenomena at proton-proton, proton-electron, electron-positron and muon-antimuon colliders are summarized.